Dosimetric Analysis and Effect of Different Definitions of Prescription Point “A” to OAR in High Dose Rate Brachytherapy for Cervical Cancer - Agrawal, Shivangi; Gupta, Shivani; Stephen PS, Meenu; Gothwal, Ravinder Singh; Meena, Ramraj; Meena, Chetna; Kakkar, Abhinav (Asian Pacific Journal of Cancer Care, 2022)
Purpose: Dosimetric analysis and effect of different definitions of prescription point “A” to OAR in high dose rate brachytherapy for cervical cancer. Methods and Materials: This retrospective comparative dosimetric study is based on the data of 25 patients with histologically proven cervical carcinoma treated with HDR (high-dose-rate) brachytherapy. Patients received 21 Gy in three fractions (7.0 Gy X three fractions) to point A (AMAN, revised Manchester definition). Further, the patients were replanned with the new point A (AABS) as per the American Brachytherapy Society/ICRU 89 which is defined on CT images. The data compiled was then compared with the data observed from point A (AMAN). Results: When AMAN normalization method was used, the mean dose to the bladder at 0.1cc, 1cc, 2cc and 5cc obtained was 1121.2±54.5, 1058.7±44.1, 875.0±38.6, 780.5±35.9, and 641.2±29.5 cGy respectively. Likewise, using the ICRU-89 point A (ABS) normalization method, the mean dose to 0.1 cc, 0.2 cc, 1 cc, 2 cc, and 5cc bladder volumes was 1178±156.1,1110.0±130.8, 921.6±111.4, 826.6±101.32, and 673.3±80.9 cGy, respectively. For the rectum, point A (MAN) normalization plans, the mean dose of 0.1 cc, 0.2 cc,1 cc, 2 cc, and 5cc rectum volumes was 680±143.5, 652.53±129.8,574.25±131.1, 530±126.9, and 452.5±121.2cGy, respectively. Likewise, using the A (ABS) plan, the mean dose of 0.1 cc, 0.2cc, 1 cc, 2 cc, and 5cc rectum volume was 707.5±148.1, 678.7±128.7, 596.2±135.6, 551.25±127.44 and 471.25±122.64 cGy respectively. The statistical mean difference of Total Reference Air Kerma rate, V100 (cc), bladder, and rectum, was found significant. Conclusion: The present study attempts to analyze the differences in rectum and bladder dose, as well as the size of the volume enclosed for prescribed Isodose curve following ICRU 38 and ABS-ICRU 89 recommendations about intracavitary cervix cancer treated with brachytherapy. With Manchester system being more static, i.e., lesser variation with geometric changes, it is preferable in comparison to ABS system.